(5x-4)(4x+9)=0

Simple and best practice solution for (5x-4)(4x+9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-4)(4x+9)=0 equation:


Simplifying
(5x + -4)(4x + 9) = 0

Reorder the terms:
(-4 + 5x)(4x + 9) = 0

Reorder the terms:
(-4 + 5x)(9 + 4x) = 0

Multiply (-4 + 5x) * (9 + 4x)
(-4(9 + 4x) + 5x * (9 + 4x)) = 0
((9 * -4 + 4x * -4) + 5x * (9 + 4x)) = 0
((-36 + -16x) + 5x * (9 + 4x)) = 0
(-36 + -16x + (9 * 5x + 4x * 5x)) = 0
(-36 + -16x + (45x + 20x2)) = 0

Combine like terms: -16x + 45x = 29x
(-36 + 29x + 20x2) = 0

Solving
-36 + 29x + 20x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-9 + -4x)(4 + -5x) = 0

Subproblem 1

Set the factor '(-9 + -4x)' equal to zero and attempt to solve: Simplifying -9 + -4x = 0 Solving -9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -4x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -4x = 0 + 9 -4x = 0 + 9 Combine like terms: 0 + 9 = 9 -4x = 9 Divide each side by '-4'. x = -2.25 Simplifying x = -2.25

Subproblem 2

Set the factor '(4 + -5x)' equal to zero and attempt to solve: Simplifying 4 + -5x = 0 Solving 4 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 0 + -4 -5x = 0 + -4 Combine like terms: 0 + -4 = -4 -5x = -4 Divide each side by '-5'. x = 0.8 Simplifying x = 0.8

Solution

x = {-2.25, 0.8}

See similar equations:

| 4(x+5)+3(x-6)= | | -136-10x=43-17x | | 45x^5+60x^2+15x= | | -2r+3=6-1/2r | | 1150+600+4x=800+400+9x | | x^2-14x-37=-8x+3 | | 1+3(-4z+7)=(z-8)-4 | | 1/2r | | m/n=p/q | | -v-4=3v | | 4(2x+3)-(x-2)= | | 2y/3-y/4=15 | | 2x^2+16x+32=17 | | 90x^2+84x^9+105= | | 7(2x+3)=4(x-5)-17 | | -v+12= | | X^4-18x^2+18=o | | -x^2-2x+1=9 | | x+3+7x-9=82 | | 5(y+-7)+-2y=1+-3[(4y+7)+-2(y+-3)] | | 10r-r= | | 5x^2+26x+32=0 | | 3(4x-2y)+2(x+2y)= | | 2x+11=6x-5-4x | | 11x-3=2x+9 | | 4x/3+2=5 | | -35x+12=28x+19 | | 2x^2+3((-2x+13)/3)^2-35=0 | | A+B+B+B+80+9=100 | | 4=ln(y+4) | | 4x+28x-32=0 | | 4(x-6)-6=x-14 |

Equations solver categories